Hybrid and evolving processes for software and systems—ICSSP 2019 special issue. Issue 1 (23rd September 2020) - Hebig, Regina; Armbrust, Ove; Sutton, Stanley M.
Abstract: The volume at hand presents the special issue of the 12th International Conference on Software and Systems Process (ICSSP) 2019, which was held in Montreal, Canada, from May 25 to 26, 2019. ICSSP 2019 is the latest in a series of conferences that have been organized by the International Software and Systems Process Association. In our evolving landscape, many companies are making efforts to move towards new technologies and tools, agile principles, and continuous integration and delivery. In doing so, they find opportunity, flexibility, and strength in evolving towards hybrid processes, which are neither purely traditional nor can count as textbook agile. This special issue focuses on hybrid processes.